PENGARUH MEDIA SOSIAL INSTAGRAM JOKO WIDODO TERHADAP ELEKTABILITAS JOKO WIDODO PADA PILPRES 2019 - Meliala, Yos Horta; Nurdiansyah, Taufik (JURNAL PUSTAKA KOMUNIKASI, 2019)
This study aims to measure "the influence of Joko Widodo's social media on the electability of Joko Widodo in the 2019 Presidential Election." As the basis of this study, the theory of Computer Mediated Communication is used. In addition, the cognitive response theory. The research method used is explanatory. While the sampling technique used is the Simple Random Sampling technique. Data was analyzed using R and T. Based on the results of the analysis showing that the influence between Joko Widodo's Instagram social media and Elektabilitas Joko Widodo is at a strong level of influence.